2016
DOI: 10.1016/j.jbiomech.2016.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Methods to study differences in cell mobility during skin wound healing in vitro

Abstract: Wound healing events which occur in humans are difficult to study in animals due to differences in skin physiology. Furthermore there are increasing restrictions in Europe for using animals for testing the therapeutic properties of new compounds. Therefore, in line with the 3Rs (reduction, refinement and replacement of test animals), a number of human in vitro models of different levels of complexity have been developed to investigate cell mobility during wound healing. Keratinocyte, melanocyte, fibroblast and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Wound closure is one of the vital steps of wound healing. The in vitro scratch wound model is a commonly used model to assess cell migration and wound closure because of its simplicity, reproducibility, and cost effectiveness . Using this model, we found that CSG enhanced the mobility of both L929 and HDFa and increased the speed of closure by more than 20%.…”
Section: Discussionmentioning
confidence: 87%
“…Wound closure is one of the vital steps of wound healing. The in vitro scratch wound model is a commonly used model to assess cell migration and wound closure because of its simplicity, reproducibility, and cost effectiveness . Using this model, we found that CSG enhanced the mobility of both L929 and HDFa and increased the speed of closure by more than 20%.…”
Section: Discussionmentioning
confidence: 87%
“…A number of recent quantitative studies have analysed in vitro wounding assays to investigate aspects of cell migration for various cell types . Human in vitro models were used in a study to investigate human skin integrity, wound closure, and scar formation . These methods included, cell culture, fibroblast and endothelial cell migration scratch assay, fibroblast chemotaxis assay, endothelial cell in vitro tube formation assay, and skin equivalent.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in vitro models have had a significant role in the study of wound healing and scar formation . This had led to a better understanding of biomarker expression, the role of keratinocytes and fibroblast activity in wound and scar development . Although the disadvantage is that, it can be difficult to extrapolate the findings of in vitro research to the in vivo wound scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore quality controls during culture that confirmed fibroblast viability (>50% confluent after approximately 1 week of culture) at the time point when fibroblasts are combined with the epithelial sheet growing on the dermis were accepted. During the following 2 weeks (3 weeks of culture total), fibroblasts migrated into the dermis (Monsuur et al, 2016). Many fibroblasts remain in the lower regions of the dermis, with few cells migrating into the upper regions.…”
Section: Discussionmentioning
confidence: 99%
“…3450, Costar, Corning Inc., New York, NY, USA) and the adherent fibroblast cells were cultured for 7–10 days in DMEM containing 5% Fetal‐Clone III and 50 μg/ml gentamycin. After 7–10 days of culturing the primary fibroblasts and epithelial sheet apart, the acellular donor dermis containing the epithelial sheet was placed on to the fibroblasts in order to allow fibroblast migration into the reticular side of the dermis (Monsuur et al, 2016). The SS and GS were further cultured air exposed in keratinocyte medium (see above), but with only 1% Fetal‐Clone III and without gentamicin.…”
Section: Methodsmentioning
confidence: 99%